Mesenchymal stem cells to treat female infertility; future perspective and challenges: A review - Yasmeen Saeed; Xiaocui Liu (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Infertility negatively impacts the overall health and social life of affected individuals and couples. Female infertility is their inability to perceive pregnancy. To date, polycystic ovary syndrome, primary ovarian insufficiency, fallopian tube obstruction, endometriosis, and intrauterine synechiae have been identified as the primary causes of infertility in women. However, despite the mutual efforts of clinicians and research scientists, the development of an effective treatment modality has met little success in combating female infertility. Intriguingly, significant research has demonstrated mesenchymal stem cells as an optimal source for treating infertility disorders. Therefore, here we attempted to capsulize to date available studies to summarize the therapeutic potential of mesenchymal stem cells in combating infertility in women by focusing on the underlying mechanism through which stem cells can reduce the effects of ovarian disorders. Furthermore, we also discussed the preclinical and clinical application of stem cell therapy, their limitation, and the future perspective to minimize these limitations.